Research on the Behavior and Mechanism of Three-Dimensional Crack Growth under Uniaxial Loading. (24th March 2021) - Zhang, Zhibo; Li, Shujie; Qin, Xuanye
Abstract : Most of the cracks in the rock masses are in a three-dimensional (3D) state, and it is always a hot topic to reveal the mechanical mechanism of 3D crack growth. In this paper, the research on the growth behavior of 3D crack is performed through laboratory experiments and numerical simulations. Cement samples with different angles of 3D crack are prepared, and the uniaxial compression experiment is carried out. The results indicate that initiation of preexisting crack with an angle of 45° is easier and shear failure characteristics of corresponding samples are obvious. Through theoretical analysis, the preexisting crack starts to grow at the end of the short axis, along the short axis end to the long axis end of the preexisting crack, the shear effect decreases gradually, and the tearing effect increases gradually. Combined with numerical simulation, the experimental and analysis results are verified, and the preexisting crack growth process is presented. The growth direction of the preexisting crack changes from perpendicular to the crack surface to parallel principal stress direction, and the maximum growth length can reach 1.2 times the minor axis radius of the preexisting crack. The research results can provide an important theoretical basis for revealing the evolution process of the cracks in rock masses.